Zagłada ogrodu – ogród Zagłady? Antony Lishak: Stars: A Story of Friendship, Courage and Small, Precious Victories. [no place], Acorn Digital Press, 2014, pp. 279 - Staroniewska‑Wątróbska, Anna (Narracje o Zagładzie [czasopismo zamknięte], 2017)
The Holocaust of the Garden – The Garden of the Holocaust? Antony Lishak: Stars: A Story of Friendship, Courage, and Small, Precious Victories. [no place], Acorn Digital Press, 2014, pp. 279. In her review, the author makes an attempt of an analysis of Antony Lishak’s novel – Stars… – from a post‑anthropocentric perspective. The book of a British writer, addressed to a young reader, is shown in the background of other literary and movie works inspired by the remarkable history of the Warsaw Zoo and its inhabitants during the Second World War, such as: Ludzie i zwierzęta by Antonina Żabińska, The Zookeeeper’s Wife by Diane Ackerman and a movie with the same title directed by Niki Caro, or Arka Czasu… by Marcin Szczygielski. Among these works is the autobiography of Antonina Żabińska, the wife of the director of the zoo, who on the pages of Ludzie i zwierzęta outlined the truly subjective portraits of animals, ahead of the theoretical concepts of ecophilosophers and ecocritics. By means of constructing parallel images of suffering (people in a ghetto and animals in the zoo) as well as the empathetic attitude of Stars’ child heroes, Antony Lishak seems to follow the path of Antonina Żabińska in his novel; however, the inconsistencies indicated by the author in the structure of narration cause the demands of posthumanism, surprisingly close to the child’s perspective, being unfulfilled. In a narrative project of consolation, the comfort is achieved only on the anthropocentric plane.